Implementasi Algoritma Sattolo Shuffle Untuk Optimasi Pengacakan Pada Game Solitaire - Surya Darma Nasution; Guidio Leonarde Ginting (Bulletin of Artificial Intelligence, 2024)
Solitaire is one of the most popular digital card games across various platforms. A critical aspect in the development of solitaire games is the card shuffling mechanism that determines the quality of gameplay experience. Suboptimal shuffling can produce predictable patterns, thereby reducing the challenge and appeal of the game. This study aims to implement the Sattolo Shuffle algorithm as a card shuffling method in solitaire games while evaluating its effectiveness in producing optimal cyclic permutations. The Sattolo Shuffle algorithm is a modification of the Fisher-Yates Shuffle algorithm specifically designed to generate cyclic permutations, where each element is guaranteed to move from its original position. Test results demonstrate that the Sattolo Shuffle algorithm can produce truly random card distributions without repeating patterns across 52 solitaire cards, consistently maintaining game difficulty levels, and providing a more dynamic playing experience compared to conventional shuffling methods. This research contributes to the development of digital card games, particularly in optimizing shuffling mechanisms to enhance gameplay quality